2017
DOI: 10.1007/s00246-017-1732-4
|View full text |Cite
|
Sign up to set email alerts
|

Blood Versus Crystalloid Cardioplegia in Pediatric Cardiac Surgery: A Systematic Review and Meta-analysis

Abstract: The benefit of blood cardioplegia (BCP) compared to crystalloid cardioplegia (CCP) is still debatable. Our aim was to systematically review and synthesize all available evidence on the use of BCP and CCP to assess if any modality provides superior outcomes in pediatric cardiac surgery. A systematic literature search of the PubMed and Cochrane databases was performed with respect to the PRISMA statement (end-of-search date: January 30th, 2017). We extracted data on study design, demographics, cardioplegia regim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 75 publications
2
13
0
Order By: Relevance
“…7,8 In our results, the cardiopulmonary bypass time in Group A is 99.4±8.46, and in Group B is 95.6±12.27.The mean cross clamp time in Group A is 72.2±89.36, and in Group B was 68±12.58 showing no statistical difference compared to different studies. 7,9 The mean ICU stay in our results in Group A is 1.28±0.46 and at the same time in Group B it is 1.72±0.61 with p-value 0.006. We found that the mean length of MV in custodial group is 4.64±0.86 and in crystalloid cardioplegia group it is 7.04±0.84 with p-value 0.000 showing a remarkable statistical difference between the two groups suggesting the superiority of HTK solution over the crystalloid cardioplegia which was similar to different studies.…”
Section: Discussionsupporting
confidence: 45%
“…7,8 In our results, the cardiopulmonary bypass time in Group A is 99.4±8.46, and in Group B is 95.6±12.27.The mean cross clamp time in Group A is 72.2±89.36, and in Group B was 68±12.58 showing no statistical difference compared to different studies. 7,9 The mean ICU stay in our results in Group A is 1.28±0.46 and at the same time in Group B it is 1.72±0.61 with p-value 0.006. We found that the mean length of MV in custodial group is 4.64±0.86 and in crystalloid cardioplegia group it is 7.04±0.84 with p-value 0.000 showing a remarkable statistical difference between the two groups suggesting the superiority of HTK solution over the crystalloid cardioplegia which was similar to different studies.…”
Section: Discussionsupporting
confidence: 45%
“…They concluded that there was no evidence of improvement in myocardial injury or clinical outcomes but were limited by the small number of patients and variability in age, preoperative cyanosis and techniques used. Similarly, Mylonas et al [18] recently identified many nonrandomized or retrospective studies on paediatric cardioplegia but few RCTs, a finding that is commonplace throughout the global paediatric cardiac surgery literature. In a recent systematic review of RCTs published since 2000, we identified few latephase clinical trials; most were small, single-centre studies of low value, uncertain quality and at risk of systematic bias [19].…”
Section: Discussionmentioning
confidence: 99%
“…Two relatively recent meta-analyses (5,24) comparing blood and non-blood cardioplegia in pediatric cardiac surgery found no difference in clinical outcomes following the use of either strategy. Of particular interest to us was that Mylonas et al found no difference in 30day mortality (5). Fang et al examined metabolic markers of myocardial protection, length of postoperative ventilation and length of intensive care unit (ICU) stay; they found that these outcomes were essentially the same irrespective of strategy used (18).…”
Section: Discussionmentioning
confidence: 99%
“…In comparing clinical outcomes between blood and nonblood cardioplegia, most randomized clinical trials have been on adult patients; pediatric trials are few (2). Some systematic reviews with meta-analyses have been conducted; however, the populations included have been significantly heterogeneous (5). Meta-analysis is a powerful and useful tool when correctly applied; elemental to proper application is the analysis of populations that are as homogenous as possible (6).…”
Section: Introductionmentioning
confidence: 99%